Gut microbiota and its metabolic products in acute respiratory distress syndrome - Zhang, Dong-Wei; Lu, Jia-Li; Dong, Bi-Ying; Fang, Meng-Ying; Xiong, Xia; Qin, Xue-Jun; Fan, Xian-Ming (Frontiers in Immunology, 2024)
The prevalence rate of acute respiratory distress syndrome (ARDS) is estimated at approximately 10% in critically ill patients worldwide, with the mortality rate ranging from 17% to 39%. Currently, ARDS mortality is usually higher in patients with COVID-19, giving another challenge for ARDS treatment. However, the treatment efficacy for ARDS is far from satisfactory. The relationship between the gut microbiota and ARDS has been substantiated by relevant scientific studies. ARDS not only changes the distribution of gut microbiota, but also influences intestinal mucosal barrier through the alteration of gut microbiota. The modulation of gut microbiota can impact the onset and progression of ARDS by triggering dysfunctions in inflammatory response and immune cells, oxidative stress, cell apoptosis, autophagy, pyroptosis, and ferroptosis mechanisms. Meanwhile, ARDS may also influence the distribution of metabolic products of gut microbiota. In this review, we focus on the impact of ARDS on gut microbiota and how the alteration of gut microbiota further influences the immune function, cellular functions and related signaling pathways during ARDS. The roles of gut microbiota-derived metabolitesin the development and occurrence of ARDS are also discussed.